A study of Indian automotive vendors using cluster analysis. (21st January 2009) - Bhardwaj, Arvind; Sharma, S.K.
The focus of this paper is on clusterising the Indian automotive vendors w.r.t. their technology up-gradation capabilities and to further study the role played by the vehicle manufacturers in developing these vendors. A structured questionnaire was developed for collecting data, which included questions related with capabilities of the organisations for adapting technology, involvement in product design for the customer, sincerity of donor company, technological strength acquired through tie up, organisational resistance to change, and customer support. Characteristics of different clusters of vendors were brought out using hierarchical cluster analysis. Four different valid clusters were synthesised based upon their characteristics and type of tie up.